An assessment of oral fluid drug screening devices. Issue 2 (3rd April 2017) - Beirness, Douglas J.; Smith, D'Arcy R.
ABSTRACT: This project was to examine point-of-contact (POC) oral fluid drug screening devices to determine the suitability of such devices for potential use in the enforcement of drug-impaired driving in Canada. Oral fluid samples were collected from a group of individuals who admitted to having recently ingested drugs as well as a number of individuals who had not been using drugs. These samples were tested on one of three oral fluid screening devices to determine the presence of cannabis, cocaine, amphetamine, methamphetamine, opioids, and benzodiazepines. Each participant also provided a second oral fluid sample that was sent to a reference laboratory for independent analysis. Comparison of the results from the oral fluid screening device and those from the laboratory analysis provided estimates of sensitivity and specificity for each of the six drugs/drug categories. Sensitivity exceeded 0.80 for cannabis, cocaine, methamphetamine, and opioids. False positive rates for these drugs/drug categories were all between 3% and 7%. Specificity exceeded 0.90 for all drugs/drug categories. These findings indicate that oral fluid screening could prove to be a valuable tool in the detection of driver drug use in Canada.